VD_FINDINFO Décision / 2015 / 923 vom 14. Dezember 2015 - VD Tribunal cantonal (2015)
RISQUE DE FUITE, RISQUE DE COLLUSION, DÉTENTION PROVISOIRE | 221 al. 1 let. a CPP (CH), 221 al. 1 let. b CPP (CH), 228 CPP (CH)